Optimizing Energy Efficiency in Multidevice Communication with Artificial Intelligence Assistance - Anouar Ben Abdennour; Mohamed Ouwais Kabaou; Flah Aymen; Belgacem Chibani Rhaimi (International Transactions on Electrical Energy Systems)
This paper seeks to improve mobile communications performance by integrating artificial intelligence (AI) techniques. The study is centered on device-to-device (D2D) communication, which has emerged as a significant aspect in the 5th generation of mobile networks (5G) and is expected to be extended to the 6th generation (6G). Based on the fuzzy system, the proposed solution tackles the critical issue of energy harvesting in D2D communication. The solution presents a support system that selects the best relay for the transmitter-receiver communication to minimize energy consumption and maximize the network’s lifetime. Minimizing energy consumption optimizes the network’s lifetime, thus providing a reliable and efficient communication system. The approach taken in this study offers a novel perspective in addressing the energy harvesting challenge in D2D communication. It is expected to have a significant impact on the performance of mobile communications.